Molecular Characterisation of MHC B-Lβ (Class II) Family Alleles in Jabalpur Dual Coloured Type Chicken using PCR- SSP - Jha, Amit Kumar; Thakur, M.S.; Sarkhel, B.C.; Parmar, S.N.S.; Tomar, S.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present investigation was taken up to study the polymorphism at MHC B-Lβ (CLASS II) family alleles using PCR- SSP in sixty Dual Coloured type chicken in the Department of Animal Genetics and Breeding, College of Veterinary Science and Animal Husbandry, Nanaji Deshmukh Veterinary Science University (NDVSU), Jabalpur. An amplified PCR product of 235 bp size observed on amplification of exon 2 of MHC B-Lβ II family gene further underwent PCR-SSP using five pairs of chicken MHC B-Lβ (class II) family haplotype specific primers. The allelic frequency of B2,B13,B15, B19 and B21 were 0.375, 0.217, 0.192, 0.217 and 0.000, respectively. The frequency of allele B2 was found to be the highest while of B15 was observed to be the lowest. The allele B21 was absent in the present studied population of Dual Coloured type birds. Chi-square values for testing correspondence between observed and expected genotypic frequencies at this locus were found to be non-significant (P>0.05) revealing Hardy -Weinberg equilibrium at this MHC locus for this populations.
Keywords: Haplotype; Dual Coloured type; PCR; PCR-SSP